2014
DOI: 10.1074/jbc.m113.534768
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Guanosine 3′,5′-Bisdiphosphate (ppGpp) Sensitivity among Guanylate Kinases of Bacteria and Plants

Abstract: Background:The ppGpp signaling system is operative in plant chloroplasts and bacteria. Results: Chloroplast and cytosolic guanylate kinases (GKs) of plants are sensitive and insensitive to ppGpp, respectively, whereas bacterial GKs show diversity in ppGpp sensitivity. Conclusion: GTP biosynthesis in chloroplasts is controlled by ppGpp. Significance: Identification of the targets of ppGpp should provide insight into biological processes regulated by this nucleotide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…This shows that the main characteristics of the stringent response are conserved between plants and bacteria. We also propose on the basis of the data that we present here, the in vitro sensitivity of plant GKs to ppGpp (Nomura et al, 2014), and the GTP initiation of plant rRNA genes (Suzuki et al, 2003;Swiatecka-Hagenbruch et al, 2007) that ppGpp is most likely to inhibit transcription by a similar mechanism to that found in B. subtilis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This shows that the main characteristics of the stringent response are conserved between plants and bacteria. We also propose on the basis of the data that we present here, the in vitro sensitivity of plant GKs to ppGpp (Nomura et al, 2014), and the GTP initiation of plant rRNA genes (Suzuki et al, 2003;Swiatecka-Hagenbruch et al, 2007) that ppGpp is most likely to inhibit transcription by a similar mechanism to that found in B. subtilis.…”
Section: Discussionmentioning
confidence: 93%
“…Chloroplasts also contain an alternative Nucleus-Encoded Polymerase (NEP), which plays a minor role in green tissues and is not inhibited by ppGpp. A recent study also provides support for a B. subtilis-like mechanism by showing that recombinant chloroplastic GK enzymes from rice (Oryza sativa) and Arabidopsis are as sensitive to inhibition by ppGpp in vitro as the B. subtilis GK with IC50s of around 30 µM (Nomura et al, 2014).…”
Section: Ppgpp Regulates Chloroplast Gene Expression By Reducing Steamentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis does not predict a mechanism for the stringent response in cyanobacteria, but several observations suggest that neither of these strategies fully accounts for the global regulation enacted by (p)ppGpp in Synechococcus. In vitro assays with Synechococcus GMK have shown that it is insensitive to (p)ppGpp (41), and its genome lacks CodY and DksA homologs as well as the (p)ppGpp-interacting motif on RNA polymerase (42). Although it is likely that alteration of GTP pools as a result of (p)ppGpp synthesis could affect cell physiology and metabolic processes, we did not observe dramatic decreases in rRNA precursor levels when (p)ppGpp levels were high (SI Appendix, Fig.…”
Section: Conservation and Adaptation Of Stringent Response Mechanisms Inmentioning
confidence: 99%
“…17) Recently, ppGpp was shown to inhibit guanylate kinase, an important enzyme in guanine nucleotide biosynthesis, in chloroplasts of plants. 18) On the other hand, nucleoside diphosphates linked to some moiety X (Nudix) hydrolases, AtNUDXs, has been shown to have ppGpp pyrophosphohydrolase activity in A. thaliana. The metabolic pathway of ppGpp without RelA/SpoT protein is shown to exist in plants.…”
Section: )mentioning
confidence: 99%